Trimetallic NiCoMo/graphene multifunctional electrocatalysts with moderate structural/electronic effects for highly efficient alkaline urea oxidation reaction. Issue 48 (28th May 2020) - Shi, Wei; Sun, Xiujuan; Ding, Rui; Ying, Danfeng; Huang, Yongfa; Huang, Yuxi; Tan, Caini; Jia, Ziyang; Liu, Enhui
Abstract : Trimetallic NiCoMo/graphene multifunctional electrocatalysts with moderate structural/electronic effects demonstrate excellent catalytic performance towards alkaline urea oxidation reaction. Abstract : Trimetallic NiCoMo/graphene (NCM/G 811) multifunctional electrocatalysts demonstrate remarkable catalytic activity, fast kinetics, a low onset potential and high stability towards alkaline urea oxidation reaction (UOR). Moderate structural/electronic effects among Ni, Co and Mo species are responsible for the outstanding catalytic behavior.